Printing ink composition, laminate and packaging material

The printing ink composition, with a binder resin, urethane resin beads, and solvent, addresses the shortcomings of existing inks by providing a layer with superior non-slip, blocking, and heat resistance for packaging materials.

JP7612916B1Active Publication Date: 2025-01-14DAINICHISEIKA COLOR & CHEMICALS MFG CO LTD

Patent Information

Application Number
JP2024050199
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-03-26
Publication Date
2025-01-14
Estimated Expiration
2044-03-26

AI Technical Summary

Technical Problem

Existing printing inks for packaging materials lack sufficient non-slip properties, blocking resistance, and heat resistance, failing to provide the necessary performance for preventing cargo collapse during transportation and ensuring consumer safety.

Method used

A printing ink composition comprising a binder resin, urethane resin beads, and an organic solvent, with specific ratios and properties, along with optional components like hydrocarbon wax and silica, to form a printing layer with enhanced non-slip, blocking, and heat resistance.

Benefits of technology

The composition achieves a printing layer with excellent non-slip properties, blocking resistance, and heat resistance, ensuring effective adhesion to substrates and maintaining print quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612916000001
    Figure 0007612916000001
  • Figure 0007612916000002
    Figure 0007612916000002
  • Figure 0007612916000003
    Figure 0007612916000003
Patent Text Reader

Abstract

Provided is a printing ink composition capable of forming a printed layer having excellent non-slip properties, blocking resistance and heat resistance. [Solution] A printing ink composition containing a binder resin (A), urethane resin beads (B), and an organic solvent (C), wherein the binder resin (A) contains at least two types selected from the group consisting of polyurethane resins, vinyl chloride-vinyl acetate copolymers, and (meth)acrylic resins, the urethane resin beads (B) have an average particle size of 1.5 to 16 μm and a glass transition temperature of -20 to 25°C, and the ratio expressed as the mass of the urethane resin beads (B) / the mass of the binder resin (A) converted into solid content is 0.1 to 1.5.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a printing ink composition, a laminate and a packaging material. [Background technology]

[0002] When packaging materials are manufactured using a base material such as a plastic film, printing is performed using printing inks such as gravure inks in order to decorate the base material or ensure necessary physical properties. Printing inks used for packaging materials are required to form a printing layer that has excellent physical properties such as adhesion to the substrate, blocking resistance, heat resistance, abrasion resistance, etc. In recent years, there has been a demand for printing inks with non-slip properties to prevent product loads from collapsing when displayed, to improve workability during transportation, and to prevent products from slipping when picked up by consumers.

[0003] Patent Document 1 reports that the slip resistance of the printed layer formed can be improved by adding a specific binder resin and a hydrocarbon wax having a penetration of 7 or more to the ink composition. Patent Document 1 also reports that the tone transfer can be improved by further adding resin beads to the ink composition. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2022-166508 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the printed layer formed from the ink composition of Patent Document 1 does not necessarily have excellent non-slip properties, blocking resistance, and heat resistance. The present invention has been made in consideration of the above circumstances, and has an object to provide a printing ink composition capable of forming a printed layer having excellent non-slip properties, blocking resistance and heat resistance, and a laminate and packaging material using the same. [Means for solving the problem]

[0006] The present invention has the following aspects. [1] A printing ink composition comprising a binder resin (A), urethane resin beads (B), and an organic solvent (C), the binder resin (A) contains at least two resins selected from the group consisting of polyurethane resins, vinyl chloride-vinyl acetate copolymers, and (meth)acrylic resins; The urethane resin beads (B) have an average particle size of 1.5 to 16 μm and a glass transition temperature of −20 to 25° C., A printing ink composition, wherein the ratio of the mass of the urethane resin beads (B) to the mass of the binder resin (A) calculated as solid content is 0.1 to 1.5. [2] The printing ink composition according to [1], wherein the content of the binder resin (A) in terms of solid content is 5 to 30 mass % based on the total mass of the printing ink composition. [3] The printing ink composition according to [1] or [2] above, wherein the static friction coefficient between the printed surfaces of a printed material obtained by forming a printing layer on a plastic film using the printing ink composition is 1.0 or more. [4] The printing ink composition according to any one of [1] to [3] above, further comprising a hydrocarbon wax. [5] The printing ink composition according to any one of [1] to [4] above, further comprising silica. [6] The printing ink composition according to any one of [1] to [5] above, further comprising a fatty acid amide. [7] The printing ink composition according to any one of [1] to [6] above, further comprising a terpene resin. [8] The printing ink composition according to any one of [1] to [7] above, further comprising a curing agent. [9] The printing ink composition according to any one of [1] to [8], wherein the organic solvent (C) contains at least two solvents selected from the group consisting of ester-based solvents, ketone-based solvents and alcohol-based solvents.

[10] The printing ink composition according to any one of [1] to [9] above, which is for gravure printing.

[11] A plastic film; a printing layer formed from the printing ink composition according to any one of [1] to

[10] above and provided on the plastic film; A laminate comprising:

[12] A packaging material comprising the laminate described in

[11] above. Effect of the Invention

[0007] According to the present invention, there can be provided a printing ink composition capable of forming a printed layer having excellent non-slip properties, blocking resistance and heat resistance, and a laminate and a packaging material using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, an embodiment of the present invention will be described. The following embodiment is merely an example for explaining the present invention, and is not intended to limit the present invention to the embodiment. The present invention can be implemented in various forms without departing from the spirit of the present invention. In this specification, the binder resin content is always calculated as a solid content. "Solid content" refers to the non-volatile content. "Non-volatile content" refers to the components excluding volatile media such as organic solvents, and is the component that will ultimately form the printing layer (ink layer). Specifically, the non-volatile content is measured in accordance with JIS K 5601-1-2:2008. In this specification, the term "printed layer" means a layer formed from a printing ink composition. In this specification, the term "printed coating film" refers to the portion of the printed layer excluding the urethane resin beads (B). In this specification, "(meth)acrylic" is meant to include both "acrylic" and "methacrylic".

[0009] [Printing ink composition] A printing ink composition according to one embodiment of the present invention (hereinafter, also simply referred to as "ink composition") contains a binder resin (A), urethane resin beads (B), and an organic solvent (C). The ink composition may further contain components other than the binder resin (A), the urethane resin beads (B), and the organic solvent (C) (hereinafter also referred to as "optional components"), as necessary.

[0010] <Binder resin (A)> The binder resin (A) contains at least two kinds of binder resins selected from the group consisting of polyurethane resins, vinyl chloride-vinyl acetate copolymers, and (meth)acrylic resins. Each resin will be described in detail later.

[0011] By combining at least two types of binder resins among polyurethane resin, vinyl chloride-vinyl acetate copolymer, and (meth)acrylic resin, it is possible to form a printing coating film with an excellent balance of various coating film properties. As a combination of at least two kinds of binder resins, a combination of a polyurethane resin and a vinyl chloride-vinyl acetate copolymer, or a combination of a (meth)acrylic resin and a vinyl chloride-vinyl acetate copolymer is preferred.

[0012] The content of the binder resin (A) (in terms of solid content) is preferably 5 to 30 mass%, more preferably 6 to 27 mass%, and particularly preferably 7 to 25 mass%, based on the total mass of the ink composition. The content of the binder resin (A) (in terms of solid content) is preferably 20 to 58 mass%, more preferably 22 to 56 mass%, and particularly preferably 25 to 54 mass%, based on the solid content of the ink composition. When the content of the binder resin (A) is equal to or greater than the above lower limit, the adhesion to the substrate and the printability of the ink composition are more excellent. When the content of the binder resin (A) is equal to or less than the above upper limit, the blocking resistance is more excellent.

[0013] The total content (solid content) of the polyurethane resin, the vinyl chloride-vinyl acetate copolymer and the (meth)acrylic resin is preferably 60% by mass or more, more preferably 70% by mass or more, and particularly preferably 80% by mass or more, based on the total mass (solid content) of the binder resin (A). The upper limit is not particularly limited, and may be 100% by mass.

[0014] When the binder resin (A) contains a polyurethane resin and a vinyl chloride-vinyl acetate copolymer, the ratio expressed by the mass of the polyurethane resin (converted into solid content) / the mass of the vinyl chloride-vinyl acetate copolymer (converted into solid content) (hereinafter also referred to as the "polyurethane resin / vinyl chloride-vinyl acetate copolymer ratio") is preferably 0.5 to 8, more preferably 1 to 7, and particularly preferably 1.5 to 6. When the polyurethane resin / vinyl chloride-vinyl acetate copolymer ratio is equal to or greater than the above lower limit, the adhesion to the substrate is more excellent. When the polyurethane resin / vinyl chloride-vinyl acetate copolymer ratio is equal to or less than the above upper limit, the blocking resistance and heat resistance are more excellent.

[0015] When the binder resin (A) contains a (meth)acrylic resin and a vinyl chloride-vinyl acetate copolymer, the ratio expressed by the mass (solid content equivalent) of the (meth)acrylic resin / the mass (solid content equivalent) of the vinyl chloride-vinyl acetate copolymer (hereinafter also referred to as the "(meth)acrylic resin / vinyl chloride-vinyl acetate copolymer ratio") is preferably 0.5 to 8, more preferably 1 to 7, and particularly preferably 1.5 to 6. When the (meth)acrylic resin / vinyl chloride-vinyl acetate copolymer ratio is equal to or greater than the above lower limit, the adhesion to the substrate is more excellent. When the (meth)acrylic resin / vinyl chloride-vinyl acetate copolymer ratio is equal to or less than the above upper limit, the blocking resistance is more excellent.

[0016] (Polyurethane resin) The polyurethane resin in the binder resin (A) may be, for example, a thermoplastic polyurethane resin soluble in an organic solvent, which is obtained by reacting a polyisocyanate compound with a polyol compound. The polyurethane resin can be produced by a known method. For example, the polyurethane resin can be obtained by reacting a polyisocyanate compound with a polyol compound, and reacting the reaction product (urethane prepolymer) with a chain extender and a reaction terminator, as necessary.

[0017] Examples of polyisocyanate compounds include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, m-xylylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4-diphenylether diisocyanate, 2-nitrodiphenyl-4,4-diisocyanate, 2,2-diphenylpropane-4,4-diisocyanate, 3,3-dimethyldiphenylmethane-4,4-diisocyanate, 4,4-diphenylpropane diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, and naphthylene. Examples of the polyisocyanate include aromatic diisocyanates such as 1,4-diisocyanate, naphthylene-1,5-diisocyanate, and 3,3-dimethoxydiphenyl-4,4-diisocyanate; aliphatic diisocyanates such as tetramethylene diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, and lysine diisocyanate; and alicyclic diisocyanates such as isophorone diisocyanate, norbornane diisocyanate, hydrogenated tolylene diisocyanate, hydrogenated xylylene diisocyanate, and hydrogenated diphenylmethane diisocyanate. In the polyurethane resin, one type of polyisocyanate compound may be used alone, or two or more types may be used in combination.

[0018] Examples of the polyol compound include polyester polyol, polycarbonate polyol, polyether polyol, etc. In the polyurethane resin, one type of polyol compound may be used alone, or two or more types may be used in combination.

[0019] Examples of the polyester polyol include polyester polyols and polyesteramide polyols obtained by dehydration polycondensation reaction between polyvalent carboxylic acids and polyhydric alcohols or secondary to tertiary amines. Specific examples of the polyvalent carboxylic acids include polycarboxylic acids such as succinic acid, adipic acid, sebacic acid, azelaic acid, terephthalic acid, isophthalic acid, orthophthalic acid, hexahydroterephthalic acid, hexahydroisophthalic acid, hexahydroorthophthalic acid, naphthalenedicarboxylic acid, and trimellitic acid, as well as their acid esters and their acid anhydrides, and one or more of these can be used. Specific examples of polyhydric alcohols include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, 1,8-octanediol, 1,9-nonanediol, diethylene glycol, dipropylene glycol, 1,4-cyclohexanedimethanol, ethylene oxide or propylene oxide adduct of bisphenol A, trimethylolpropane, glycerin, and low molecular weight alcohol compounds such as pentaerythritol; and low molecular weight amino alcohol compounds such as monoethanolamine and diethanolamine, and one or more of these can be used. Specific examples of secondary and tertiary amines include low molecular weight amine compounds such as hexamethylenediamine, xylylenediamine, and isophoronediamine, and one or more of these can be used. Further, examples of the polyester polyol include lactone-based polyester polyols obtained by ring-opening polymerization of cyclic ester (lactone) monomers such as ε-caprolactone and γ-valerolactone using a low molecular weight alcohol compound and a low molecular weight amino alcohol compound as an initiator.

[0020] Examples of the polycarbonate polyol include those obtained by dehydrochlorination reaction between a low molecular weight alcohol compound and phosgene; and those obtained by transesterification reaction between a low molecular weight alcohol compound and a carbonic acid diester. Examples of the low molecular weight alcohol compound include the same compounds used in the synthesis of polyester polyols. Examples of the carbonic acid diester include diethylene carbonate, dimethyl carbonate, diethyl carbonate, and diphenyl carbonate.

[0021] Examples of polyether polyols include those obtained by ring-opening polymerization of cyclic ethers (e.g., alkylene oxides such as ethylene oxide, propylene oxide, butylene oxide, and tetrahydrofuran) using at least one initiator selected from the group consisting of low molecular weight alcohol compounds, low molecular weight amine compounds, low molecular weight amino alcohol compounds, and phenols (e.g., polyoxyethylene polyols, polyoxypropylene polyols, polytetramethylene ether polyols, polyoxyethylene polyoxypropylene polyols, etc.). Examples of low molecular weight alcohol compounds, low molecular weight amine compounds, and low molecular weight amino alcohol compounds include those similar to those used in the synthesis of polyester polyols. Furthermore, examples of polyester ether polyols using the above-mentioned polyester polyols or polycarbonate polyols as initiators include.

[0022] As the chain extender, a compound having two or more functional groups (amino group, hydroxyl group, etc.) capable of reacting with an isocyanate group in the molecule can be used. Examples of the chain extender include diamine compounds such as ethylenediamine, 1,3-propylenediamine, 1,4-butylenediamine, hexamethylenediamine, isophoronediamine, and 2-ethylaminoethylamine; polyamine compounds such as diethylenetriamine and triethylenetetramine; low molecular weight diol compounds such as ethylene glycol, propylene glycol, butylene glycol, diethylene glycol, and triethylene glycol; aminoethylethanolamine, and aminopropylethanolamine. In the polyurethane resin, one type of chain extender may be used alone, or two or more types may be used in combination.

[0023] Examples of the reaction terminator include monoalkylamines such as n-propylamine and n-butylamine, dialkylamines such as di-n-butylamine, alkanolamines such as monoethanolamine and diethanolamine, and monoalcohols such as methanol and ethanol. In the polyurethane resin, one type of reaction terminator may be used alone, or two or more types may be used in combination.

[0024] The glass transition temperature of the polyurethane resin is preferably −70 to 0° C., more preferably −60 to −10° C., and particularly preferably −50 to −20° C. When the glass transition temperature of the polyurethane resin is equal to or higher than the lower limit, the blocking resistance and heat resistance are more excellent. When the glass transition temperature of the polyurethane resin is equal to or lower than the upper limit, the adhesion to the substrate is more excellent. In this specification, the glass transition temperature is determined in accordance with JIS K 7121 from the intersection point between the baseline and the tangent to the endothermic curve in a curve (DSC curve) obtained by heating 10 mg of a sample from -100°C to 160°C at a temperature rate of 20°C / min using a differential scanning calorimeter.

[0025] The weight average molecular weight of the polyurethane resin is preferably 10,000 to 100,000, more preferably 15,000 to 90,000, and particularly preferably 20,000 to 80,000. When the weight average molecular weight of the polyurethane resin is equal to or more than the lower limit, the blocking resistance and heat resistance are more excellent. When the weight average molecular weight of the polyurethane resin is equal to or less than the upper limit, the adhesion to the substrate is more excellent. In this specification, the weight average molecular weight is a value calculated in terms of standard polystyrene by gel permeation chromatography (GPC).

[0026] The hydroxyl value of the polyurethane resin is preferably 50 mgKOH / g or less, more preferably 30 mgKOH / g or less, and particularly preferably 20 mgKOH / g or less. When the hydroxyl value of the polyurethane resin is equal to or less than the above upper limit, the blocking resistance and the stability of the ink composition are more excellent. In this specification, the hydroxyl value is a value measured in accordance with JIS K 1557-1.

[0027] The amine value of the polyurethane resin is preferably 10 mgKOH / g or less, more preferably 5 mgKOH / g or less, and particularly preferably 3 mgKOH / g or less. When the amine value of the polyurethane resin is equal to or less than the above upper limit, the printability is more excellent. In this specification, the amine value is a value measured by neutralization titration using hydrochloric acid in accordance with JIS K 7237.

[0028] The storage modulus (E'; dynamic storage modulus) of the polyurethane resin at a temperature of 100°C and a frequency of 11 Hz is preferably not more than 20, more preferably not more than 10, and particularly preferably not more than 5. When the storage modulus of the polyurethane resin is not more than the above upper limit, the adhesion to the substrate is superior. In this specification, the storage modulus is a value obtained by measuring the dynamic viscoelasticity of a dry film of a sample (film-like sample) using a dynamic viscoelasticity measuring device at a temperature of 100° C. and a frequency of 11 Hz.

[0029] (Vinyl chloride-vinyl acetate copolymer) A vinyl chloride-vinyl acetate copolymer is a polymer obtained by polymerizing polymerizable monomers including vinyl chloride and vinyl acetate, and contains vinyl chloride units and vinyl acetate units. The vinyl chloride-vinyl acetate copolymer may contain a polymerizable monomer unit (other polymerizable monomer) other than the vinyl chloride unit and the vinyl acetate unit, if necessary. The other polymerizable monomer is not particularly limited as long as it is copolymerizable with vinyl chloride and vinyl acetate.

[0030] Examples of vinyl chloride-vinyl acetate copolymers include vinyl chloride-vinyl acetate copolymers, vinyl chloride-vinyl acetate-vinyl alcohol copolymers, vinyl chloride-vinyl acetate-(meth)acrylic acid hydroxyalkyl ester copolymers, and vinyl chloride-vinyl acetate-unsaturated dicarboxylic acid copolymers. Among these, vinyl chloride-vinyl acetate-vinyl alcohol copolymers are preferred. The vinyl chloride-vinyl acetate copolymers may be used alone or in combination of two or more.

[0031] The content of vinyl chloride units is preferably 50 to 98% by mass, more preferably 70 to 98% by mass, and particularly preferably 80 to 95% by mass, based on the total mass of the vinyl chloride-vinyl acetate copolymer. When the content of vinyl chloride units is equal to or greater than the lower limit, blocking resistance is more excellent. When the content of vinyl chloride units is equal to or less than the upper limit, adhesion to a substrate and kneading resistance are more excellent.

[0032] The content of vinyl acetate units is preferably 0.1 to 20% by mass, more preferably 0.3 to 10% by mass, and particularly preferably 0.5 to 5% by mass, based on the total mass of the vinyl chloride-vinyl acetate copolymer. When the content of vinyl acetate units is equal to or greater than the lower limit, adhesion to the substrate and kneading resistance are more excellent. When the content of vinyl acetate units is equal to or less than the upper limit, blocking resistance is more excellent.

[0033] The glass transition temperature of the vinyl chloride-vinyl acetate copolymer is preferably 40 to 110° C., more preferably 50 to 100° C., and particularly preferably 60 to 90° C. When the glass transition temperature of the vinyl chloride-vinyl acetate copolymer is equal to or higher than the lower limit, the blocking resistance and heat resistance are more excellent. When the glass transition temperature of the vinyl chloride-vinyl acetate copolymer is equal to or lower than the upper limit, the adhesion to the substrate is more excellent.

[0034] The number average molecular weight of the vinyl chloride-vinyl acetate copolymer is preferably 10,000 to 100,000, more preferably 15,000 to 80,000, and particularly preferably 20,000 to 50,000. When the number average molecular weight of the vinyl chloride-vinyl acetate copolymer is equal to or higher than the lower limit, the blocking resistance and heat resistance are more excellent. When the number average molecular weight of the vinyl chloride-vinyl acetate copolymer is equal to or lower than the upper limit, the adhesion to the substrate is more excellent. In this specification, the number average molecular weight is a value calculated as standard polystyrene by gel permeation chromatography (GPC).

[0035] ((Meth)acrylic resin) The (meth)acrylic resin is a polymer formed by polymerizing a polymerizable monomer containing a (meth)acrylic acid ester, and contains a (meth)acrylic acid ester unit. The (meth)acrylic resin may contain a polymerizable monomer unit (another polymerizable monomer) other than the (meth)acrylic acid ester unit, if necessary. The other polymerizable monomer is not particularly limited as long as it is copolymerizable with the (meth)acrylic acid ester. The (meth)acrylic resin may be modified.

[0036] Examples of the (meth)acrylic resin include homopolymers of (meth)acrylic acid esters, copolymers of multiple types of (meth)acrylic acid esters, copolymers of (meth)acrylic acid esters and (meth)acrylic acid esters with other monomers, urethane-modified (meth)acrylic resins, and silicone-modified (meth)acrylic resins. One type of (meth)acrylic resin may be used alone, or two or more types may be used in combination.

[0037] Examples of (meth)acrylic acid esters include, but are not limited to, (meth)acrylic acid alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate; (meth)acrylic acid aralkyl esters such as benzyl (meth)acrylate; (meth)acrylic acid aryl esters such as phenyl (meth)acrylate and naphthyl (meth)acrylate; (meth)acrylic acid hydroxyalkyl esters such as 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate. The above (meth)acrylic acid esters may be used alone or in combination of two or more.

[0038] Examples of the other polymerizable monomers include, but are not limited to, styrene-based monomers such as styrene, α-methylstyrene, vinyltoluene, and derivatives thereof; unsaturated carboxylic acid-based monomers such as (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, and crotonic acid; acrylamide, methacrylamide, acrylonitrile, and methacrylonitrile. The above-mentioned other polymerizable monomers may be used alone or in combination of two or more.

[0039] The (meth)acrylic resin preferably has a hydroxyl group and is preferably a (meth)acrylic polyol. The hydroxyl value of the (meth)acrylic resin is preferably 1 to 130 mgKOH / g, more preferably 10 to 120 mgKOH / g, and particularly preferably 50 to 110 mgKOH / g. When the hydroxyl value of the (meth)acrylic resin is equal to or greater than the lower limit, the adhesion to the substrate is superior. When the hydroxyl value of the (meth)acrylic resin is equal to or less than the upper limit, the blocking resistance and the stability of the ink composition are superior.

[0040] The acid value of the (meth)acrylic resin is preferably 30 mgKOH / g or less, more preferably 20 mgKOH / g or less, and particularly preferably 10 mgKOH / g or less. When the acid value of the (meth)acrylic resin is the above upper limit or less, the stability of the ink composition is more excellent. In this specification, the acid value is a value measured in accordance with JIS K 1557.

[0041] The glass transition temperature of the (meth)acrylic resin is preferably 5 to 100° C., more preferably 10 to 70° C., and particularly preferably 15 to 40° C. When the glass transition temperature of the (meth)acrylic resin is equal to or higher than the above lower limit, the blocking resistance and heat resistance are more excellent. When the glass transition temperature of the (meth)acrylic resin is equal to or lower than the above upper limit, the adhesion to the substrate is more excellent.

[0042] The weight average molecular weight (Mw) of the (meth)acrylic resin is preferably 10,000 to 300,000, more preferably 20,000 to 280,000, and particularly preferably 40,000 to 250,000. When the weight average molecular weight (Mw) of the (meth)acrylic resin is equal to or greater than the lower limit, the blocking resistance and heat resistance are more excellent. When the weight average molecular weight (Mw) of the (meth)acrylic resin is equal to or less than the upper limit, the adhesion to the substrate is more excellent.

[0043] <Urethane resin beads (B)> The urethane resin beads (B) are polyurethane resin formed into beads. In this embodiment, when a printed layer is formed using the ink composition, the urethane resin beads (B) are exposed from the surface of the printed coating film. The exposed urethane resin beads (B) interfere with each other, making it difficult for the printed matter to slip against each other, thereby exhibiting non-slip properties.

[0044] The average particle size of the urethane resin beads (B) is 1.5 to 16 μm, preferably 2 to 12 μm, and particularly preferably 2.5 to 8 μm. When the average particle size of the urethane resin beads (B) is equal to or greater than the above lower limit, the non-slip properties are excellent. When the average particle size of the urethane resin beads (B) is equal to or less than the above upper limit, the heat resistance, blocking resistance, abrasion resistance, adhesion to the substrate, and printability are excellent. In this specification, the average particle size of the urethane resin beads (B) means the particle size at an integrated value of 50% (D50) in the volume-based particle size distribution, and can be determined by a laser diffraction / scattering method.

[0045] The glass transition temperature of the urethane resin beads (B) is −20 to 25° C., preferably −17 to 20° C., and particularly preferably −15 to 10° C. When the glass transition temperature of the urethane resin beads (B) is not less than the above lower limit, the heat resistance and blocking resistance are excellent. When the glass transition temperature of the urethane resin beads (B) is not more than the above upper limit, the non-slip properties are excellent.

[0046] The ratio (hereinafter also referred to as "(B) / (A)") expressed as the mass of the urethane resin beads (B) / the mass of the binder resin (A) converted into solid content is 0.1 to 1.5, preferably 0.3 to 1.2, and particularly preferably 0.5 to 1. When (B) / (A) is equal to or more than the above lower limit, the non-slip properties are excellent. When (B) / (A) is equal to or less than the above upper limit, the heat resistance and printability are excellent.

[0047] <Organic solvent (C)> The organic solvent (C) may be any one that does not dissolve the urethane resin beads (B), and may be appropriately selected from known organic solvents. For example, ketone-based solvents, hydrocarbon-based solvents, ester-based solvents, ether-based solvents, glycol ether-based solvents, and alcohol-based solvents may be mentioned, and one of these may be used alone or two or more of them may be used in combination.

[0048] Examples of the ketone solvent include acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone. Examples of the hydrocarbon solvent include aromatic hydrocarbon solvents such as toluene and xylene; aliphatic hydrocarbon solvents such as n-hexane, n-heptane, and n-octane; and alicyclic hydrocarbon solvents such as cyclohexane, methylcyclohexane, and cyclooctane. Examples of the ester solvent include methyl acetate, ethyl acetate, n-propyl acetate, n-butyl acetate, and isobutyl acetate. Examples of the ether solvent include tetrahydrofuran, dioxane, diethyl ether, and methyl ethyl ether. Examples of glycol ether solvents include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, and propylene glycol monomethyl ether. Examples of alcohol-based solvents include monohydric alcohols such as methanol, ethanol, n-propanol, isopropanol, and n-butanol; and polyhydric alcohols such as ethylene glycol, propylene glycol, and glycerin.

[0049] From an environmental perspective, the organic solvent (C) preferably does not substantially contain toluene, and particularly preferably does not substantially contain aromatic hydrocarbon solvents. That is, the ink composition preferably does not substantially contain toluene, and particularly preferably does not substantially contain aromatic hydrocarbon solvents. "Substantially does not contain" means that it is not intentionally blended. The ink composition may contain a small amount of aromatic hydrocarbon solvents such as toluene due to contamination of raw materials, etc., but it is preferable that it does not contain any aromatic hydrocarbon solvents.

[0050] From the viewpoint of the stability of the ink composition, the organic solvent (C) preferably contains at least two types selected from the group consisting of ester-based organic solvents, ketone-based organic solvents, and alcohol-based organic solvents. As a combination of at least two organic solvents, a combination of an ester-based organic solvent and an alcohol-based organic solvent, or a combination of an ester-based organic solvent, a ketone-based organic solvent and an alcohol-based organic solvent is preferable.

[0051] When the organic solvent (C) contains at least two selected from the group consisting of ester-based solvents, ketone-based solvents, and alcohol-based solvents, the content of the ester-based organic solvent is preferably 5 to 80 mass% based on the total mass of the organic solvent (C). The content of the ketone-based organic solvent is preferably 5 to 80 mass% based on the total mass of the organic solvent (C). The content of the alcohol-based organic solvent is preferably 0 to 50 mass% based on the total mass of the organic solvent (C).

[0052] The content of the organic solvent (C) in the ink composition can be appropriately set taking into consideration the content of the solids in the ink composition. The solid content of the ink composition is, for example, 20 to 60% by mass with respect to the total mass of the ink composition.

[0053] <Optional ingredients> Examples of optional components include hydrocarbon wax, silica, fatty acid amide, terpene resin, hardener, pigment, pigment derivative, extender pigment, cellulose resin, rosin derivative, chelating agent, chlorinated polyolefin, antisettling agent, ultraviolet absorber, antioxidant, antistatic agent, leveling agent, thickener, defoamer, plasticizer, dispersant, stabilizer, etc. These optional components may be used alone or in combination of two or more. The ink composition may be a so-called medium ink composition that does not contain a pigment.

[0054] (Hydrocarbon wax) To further improve rub resistance, the ink composition may contain a hydrocarbon wax. Examples of the hydrocarbon wax include polyethylene wax, Fischer-Tropsch wax, paraffin wax, microstalline wax, and polypropylene wax. Among them, polyethylene wax and Fischer-Tropsch wax are preferred. Examples of the polyethylene wax include high-density polymerized polyethylene, low-density polymerized polyethylene, oxidized polyethylene, acid-modified polyethylene, and special monomer-modified polyethylene. Fischer-Tropsch wax is a wax produced by the Fischer-Tropsch process using carbon monoxide and hydrogen as raw materials, and has a nearly saturated, unbranched, linear molecular structure. These hydrocarbon waxes may be used alone or in combination of two or more.

[0055] The penetration (hardness) of the hydrocarbon wax at 25° C. is preferably from 0.1 to 30, more preferably from 0.1 to 28, and particularly preferably from 0.1 to 25. When the penetration (hardness) of the hydrocarbon wax is equal to or less than the above upper limit, the abrasion resistance is more excellent. In this specification, the penetration (hardness) is a value measured in accordance with JIS K2207.

[0056] The melting point of the hydrocarbon wax is preferably 50 to 160° C., more preferably 80 to 150° C., and particularly preferably 100 to 140° C. When the melting point of the hydrocarbon wax is equal to or higher than the lower limit, the heat resistance and blocking resistance are more excellent. When the melting point of the hydrocarbon wax is equal to or lower than the upper limit, the abrasion resistance is more excellent.

[0057] When the ink composition contains a hydrocarbon wax, the content of the hydrocarbon wax is preferably 0.3 to 10 mass%, more preferably 1 to 8 mass%, and particularly preferably 2 to 5 mass%, based on the solid content of the ink composition. When the content of the hydrocarbon wax is equal to or more than the above lower limit, the abrasion resistance is more excellent. When the content of the hydrocarbon wax is equal to or less than the above upper limit, the printability and heat resistance are more excellent.

[0058] (silica) For the purpose of imparting a matte finish and further improving blocking resistance, silica can be contained in the ink composition. Silica may be either natural or synthetic. Synthetic products may be synthesized by either dry or wet methods. Dry methods include combustion and arc methods, and wet methods include precipitation and gel methods. Silica may be synthesized by either method. Silica may be either crystalline or non-crystalline, and may be either hydrophobic or hydrophilic. These silicas may be used alone or in combination of two or more types.

[0059] The average particle size of the silica is preferably 0.1 to 10 μm, more preferably 1 to 8 μm, and particularly preferably 2 to 6 μm. When the average particle size of the silica is equal to or greater than the lower limit, it is easy to obtain a matte finish and a further improved blocking resistance. When the average particle size of the silica is equal to or less than the upper limit, the printability is more excellent. In this specification, the average particle size of silica means the particle size at an integrated value of 50% (D50) in the volume-based particle size distribution, and can be determined by a laser diffraction / scattering method.

[0060] When the ink composition contains silica, the content of silica is preferably 1 to 10 mass%, more preferably 1.5 to 8 mass%, and particularly preferably 2 to 5 mass%, based on the solid content of the ink composition. When the content of silica is equal to or more than the lower limit, it is easy to obtain the effect of imparting a matte finish and the effect of further improving blocking resistance. When the content of silica is equal to or less than the upper limit, the ink fluidity and printability are more excellent.

[0061] (Fatty acid amides) For the purpose of further improving the releasability and blocking resistance, the ink composition may contain a fatty acid amide. Examples of fatty acid amides include saturated fatty acid monoamides such as lauric acid amide, palmitic acid amide, stearic acid amide, oleic acid amide, erucic acid amide, behenic acid amide, hydroxystearic acid amide, and N-stearyl stearic acid amide; unsaturated fatty acid monoamides such as N-oleyl palmitic acid amide, N-stearyl oleic acid amide, and N-oleyl stearic acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, and ethylene bisstearic acid. Examples of the fatty acid bisamide include saturated fatty acid bisamides such as ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, N,N'-distearyl adipic acid amide, and N,N'-distearyl sebacic acid amide; and unsaturated fatty acid bisamides such as ethylene bisoleic acid amide, ethylene biserucic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipic acid amide, and N,N'-dioleyl sebacic acid amide. These fatty acid amides may be used alone or in combination of two or more.

[0062] When the ink composition contains a fatty acid amide, the content of the fatty acid amide is preferably 0.5 to 5 mass%, more preferably 0.8 to 4 mass%, and particularly preferably 1 to 3 mass%, based on the solid content of the ink composition. When the content of the fatty acid amide is equal to or more than the lower limit, the releasability and blocking resistance are more excellent. When the content of the fatty acid amide is equal to or less than the upper limit, the stability of the ink composition at low temperatures is more excellent.

[0063] (Terpene resin) For the purpose of further improving adhesion to a substrate, a terpene resin may be contained in the ink composition. Examples of the terpene resin include polyterpene resin, aromatic modified terpene resin, and terpene phenol resin. The polyterpene resin is a resin whose main component is a structural unit derived from a terpene monomer. The aromatic modified terpene resin is a resin obtained by modifying a polyterpene resin with an aromatic monomer. The terpene phenol resin is a resin obtained by copolymerizing a terpene monomer and a phenol. These terpene resins may be used alone or in combination of two or more kinds.

[0064] The softening point of the terpene resin is preferably 80 to 200° C., more preferably 90 to 190° C., and particularly preferably 100 to 180° C. When the softening point of the terpene resin is equal to or higher than the lower limit, the blocking resistance and heat resistance are more excellent. When the softening point of the terpene resin is equal to or lower than the upper limit, the adhesion to the substrate is more excellent. In this specification, the softening point is a value measured in accordance with JIS K 2207.

[0065] The acid value of the terpene resin is preferably 10 to 150 mgKOH / g, more preferably 20 to 100 mgKOH / g, and particularly preferably 30 to 80 mgKOH / g. When the acid value of the terpene resin is equal to or higher than the lower limit, the adhesion to the substrate is more excellent. When the acid value of the terpene resin is equal to or lower than the upper limit, the stability of the ink composition is more excellent.

[0066] When the ink composition contains a terpene resin, the content of the terpene resin is preferably 0.5 to 10 mass%, more preferably 1 to 8 mass%, and particularly preferably 2 to 5 mass%, based on the solid content of the ink composition. When the content of the terpene resin is equal to or more than the lower limit, the adhesion to the substrate is more excellent. When the content of the terpene resin is equal to or less than the upper limit, the blocking resistance and heat resistance are more excellent.

[0067] (hardening agent) For the purpose of further improving adhesion to a substrate, heat resistance, and abrasion resistance, the ink composition may contain a curing agent.

[0068] As the curing agent, an isocyanate-based curing agent is preferred. The isocyanate-based curing agent is a compound having two or more isocyanate groups in one molecule. Examples of the isocyanate-based curing agent include aromatic diisocyanates such as 4,4'-diphenylmethane diisocyanate (MDI), 2,2'-MDI, 2,4'-MDI, 2,4-tolylene diisocyanate (TDI), 2,6-TDI, m-xylylene diisocyanate (XDI), and 1,4-phenylene diisocyanate; isophorone diisocyanate (IPDI), 1,3-bis(isocyanatomethyl)cyclohexane (hydrogenated XDI), dicyclohexylmethane-4,4'-diisocyanate ( Examples of the isocyanate curing agent include alicyclic diisocyanates such as 1-methylcyclohexane-2,4-diisocyanate (hydrogenated TDI) and the like; aliphatic diisocyanates such as tetramethylene diisocyanate, hexamethylene diisocyanate (HDI) and the like, and isocyanate prepolymers such as adducts of various diisocyanates, isocyanurates of various diisocyanates, biuret bodies of HDI and allophanate bodies of HDI. These isocyanate curing agents may be used alone or in combination of two or more kinds.

[0069] When the ink composition contains a curing agent, the content of the curing agent is preferably 1 to 10 mass %, more preferably 2 to 9 mass %, and particularly preferably 3 to 8 mass %, based on the solid content of the ink composition. When the content of the curing agent is equal to or more than the lower limit, the adhesion to the substrate, heat resistance, and abrasion resistance are more excellent. When the content of the curing agent is equal to or less than the upper limit, the blocking resistance and stability of the ink composition are more excellent.

[0070] <Static friction coefficient> The ink composition of the present embodiment has a static friction coefficient of 1.0 or more, more preferably 1.1 or more, and particularly preferably 1.2 or more between the printed surfaces of a printed material formed by forming a printed layer on a plastic film using the ink composition of the present embodiment. The upper limit of the static friction coefficient is not particularly limited, but is, for example, 2.0. If the static friction coefficient is equal to or more than the lower limit, it is useful for applications requiring non-slip properties. In this specification, the static friction coefficient is measured in accordance with JIS K 7125. As an index of non-slip property, in addition to the static friction coefficient, there are also the dynamic friction coefficient and the slip angle, but the static friction coefficient is particularly important.

[0071] <Manufacturing method> The ink composition of the present embodiment can be obtained, for example, by mixing the binder resin (A), urethane resin beads (B), an organic solvent (C), and, if necessary, optional components, and, if necessary, subjecting the mixture to a dispersion treatment. The method for mixing the components is not particularly limited, and the components can be mixed by various methods. The method of dispersion treatment is not particularly limited, and can be carried out using a known dispersing machine. Examples of dispersing machines include paint shakers, ball mills, attritors, sand mills, bead mills, dyno mills, roll mills, ultrasonic mills, and high-pressure collision dispersing machines. In this case, one type of dispersing machine can be used to carry out dispersion treatment once or multiple times, or two or more types of dispersing machines can be used in combination to carry out dispersion treatment multiple times. When the ink composition contains a curing agent, it is preferable to premix the components other than the curing agent, and mix the mixture with the curing agent just before applying the ink composition to a substrate (such as a plastic film) to prepare an ink composition. The time from mixing the mixture with the curing agent to applying the ink composition to a substrate varies depending on the type of curing agent, but is, for example, within 6 hours.

[0072] <Action and effect> The ink composition of the present embodiment described above contains the above-mentioned binder resin (A), urethane resin beads (B), and organic solvent (C), and since (B) / (A) is 0.1 to 1.5, a printed layer excellent in non-slip properties, blocking resistance, heat resistance, and abrasion resistance can be formed. In addition, the adhesion of the printed layer to the substrate and abrasion resistance, and the printability of the ink composition are also excellent.

[0073] <Application> The ink composition of the present embodiment is used to form a printed layer on a substrate. For example, the ink composition can be diluted with an organic solvent as necessary, applied onto a substrate, and dried to form a printed layer.

[0074] The substrate is preferably a plastic film, since it is highly useful to impart non-slip properties to the substrate. Examples of plastic films include polyolefin (e.g., polyethylene (PE), polypropylene (PP), etc.) films, polyester (e.g., polyethylene terephthalate (PET), etc.) films, polystyrene (PS) films, oriented polypropylene (OPP) films, polyamide (NY) films, etc. These plastic films may be used alone or in combination of two or more.

[0075] The organic solvent used to dilute the ink composition is preferably the same as the organic solvent (C) in the ink composition. The method for applying the ink composition or a diluted solution thereof may be a known method, such as gravure printing, flexographic printing, brush coating, gravure coater method, die coater method, bar coater method, spray coating method, flow coating method, dip coating method, spin coating method, curtain coating method, etc. Of these, gravure printing is preferred. The drying method may be any method capable of removing the organic solvent (C) from the ink composition, and examples of the drying method include heat drying and natural drying. The heating temperature for heat drying is, for example, 40 to 70°C.

[0076] The average diameter of the urethane resin beads (B) in the ink composition of this embodiment is usually larger than the thickness of the printed coating film of the printed layer formed using the ink composition. The thickness of the printed coating film varies depending on the application method, but for example, in the case of gravure printing, it is about 1 to 3 μm. The thickness of the printed layer is thicker than the thickness of the printed coating film by the amount of the urethane resin beads (B), and is, for example, 2 to 8 μm. In this specification, the thickness of the printed layer is the average value measured at 10 points using a high-precision digital micrometer (trade name: MDH-25MB) manufactured by Mitutoyo Corporation. The printed layer may be provided on one side or both sides of the substrate. The printed layer may be provided so as to cover the entire substrate or to cover a part of the substrate.

[0077] A laminate in which a printed layer is formed on a plastic film using the ink composition of this embodiment can be used, for example, as a packaging material, particularly a soft packaging material. Here, "flexible packaging" refers to packaging material made of a flexible material, i.e., flexible packaging, which is used for packaging food, daily necessities, etc. When the laminate is a packaging material, from the viewpoint of the usefulness of imparting non-slip properties to a plastic film, it is preferable that a printed layer formed from the ink composition of the present embodiment is located on the surface of the packaging material. Here, the surface of the packaging material is the surface opposite to the surface (rear surface) that comes into contact with the packaged item when the packaged item is packaged with the packaging material to form a package. EXAMPLES

[0078] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention. Examples 14 and 15 are reference examples.

[0079] [Raw materials used] The following raw materials were used: <Binder resin (A)> A1-1: Polyurethane resin (manufactured by San Nopco Ltd., product name "Sanpren IB", glass transition temperature: -38°C, hydroxyl value: 4.2mgKOH / g). A1-2: Polyurethane resin (manufactured by San Nopco Ltd., product name "Sanpren IB", glass transition temperature: -45°C, hydroxyl value: 11.1 mgKOH / g). A2-1: (Meth)acrylic resin (manufactured by Mitsubishi Chemical Corporation, product name "Dianal AL", glass transition temperature: 25°C, hydroxyl value: 100 mg KOH / g). A3-1: Vinyl chloride-vinyl acetate copolymer (Nissin Chemical Industry Co., Ltd., product name "Solbine", glass transition temperature: 78°C). A3-2: Vinyl chloride-vinyl acetate copolymer (Nissin Chemical Industry Co., Ltd., product name "Solbine", glass transition temperature: 76°C).

[0080] <Resin beads (B)> B-1: Urethane resin beads (manufactured by Negami Chemical Industrial Co., Ltd., product name "Art Pearl C-1000T", average particle size: 3 μm, glass transition temperature: -13°C). B-2: Urethane resin beads (manufactured by Negami Chemical Industrial Co., Ltd., product name "Art Pearl C-800T", average particle size: 6 μm, glass transition temperature: -13°C). B-3: Urethane resin beads (manufactured by Negami Chemical Industrial Co., Ltd., product name "Art Pearl C-400T", average particle size: 15 μm, glass transition temperature: -13°C). B-4: Urethane resin beads (manufactured by Negami Chemical Industrial Co., Ltd., product name "Art Pearl MM-120T", average particle size: 2 μm, glass transition temperature: 22°C). B-5: Urethane resin beads (manufactured by Negami Chemical Industrial Co., Ltd., product name "Art Pearl MM-110SMA", average particle size: 1 μm). B-6: Urethane resin beads (manufactured by Negami Chemical Industrial Co., Ltd., product name "Art Pearl C-300T", average particle size: 22 μm, glass transition temperature: -13°C). B-7: Urethane resin beads (manufactured by Negami Chemical Industrial Co., Ltd., product name "Art Pearl P-800T", average particle size: 6 μm, glass transition temperature: -34°C). B-8: Urethane resin beads (manufactured by Negami Chemical Industrial Co., Ltd., product name "Art Pearl CE-800T", average particle size: 6 μm, glass transition temperature: 34°C). B-9: Cross-linked methyl methacrylate resin beads (manufactured by Sekisui Chemical Co., Ltd., product name "Techpolymer MBX-5", average particle size: 5 μm). B-10: Benzocyanamine-formaldehyde condensate resin beads (manufactured by Nippon Shokubai Co., Ltd., product name "Eposter M05", average particle size: 5 μm).

[0081] <Organic solvent (C)> C-1: A mixed solvent of ethyl acetate:methyl ethyl ketone:isopropanol = 2:2:1 (mass ratio). C-2: A mixed solvent of ethyl acetate:isopropanol = 4:1 (mass ratio).

[0082] <Optional ingredients> Hydrocarbon wax: Mitsui Chemicals, Inc., product name "HIWAX 220P", penetration: 13, melting point: 110℃. Silica: Manufactured by Tosoh Silica Corporation, product name "Nipsil E-220", average particle size: 4.9 μm. Fatty acid amide: NOF Corporation, product name "Alflow S-10". Terpene resin: manufactured by Arakawa Chemical Industries, Ltd., product name "Tamanol 803L", softening point: 150°C, acid value: 50 mgKOH / g. Hardener: Polyisocyanate (manufactured by Mitsui Chemicals, Inc., product name "Takenate D-160N"). · Extender pigment: Calcium carbonate (manufactured by Shiraishi Kogyo Co., Ltd., product name "Homocal-D").

[0083] [Examples 1 to 16 and Comparative Examples 1 to 11] <Preparation of Ink Composition> According to the compositions shown in Tables 1 to 5, the binder resin (A), resin beads (B), organic solvent (C), and optional components (except for the curing agent) were mixed, and the resulting mixture was kneaded with a paint shaker, and the curing agent was further mixed in to obtain an ink composition. The curing agent was mixed just before dilution in the production of the next printed matter. In Tables 1 to 5, the contents of components other than the organic solvent (C) are calculated on a solid content basis. A blank space indicates that the component is not included.

[0084] <Creating printed matter> As a substrate, a PET film (manufactured by Toyobo Co., Ltd., product name "E5102", thickness: 25 μm) having one side subjected to a corona discharge treatment was prepared. The prepared ink composition was diluted with the same organic solvent (C) as that blended in the ink composition so that the viscosity at 25°C measured using Zahn cup #3 was 17 seconds. The diluted ink composition was applied to the corona discharge treated surface of the substrate using a gravure printing machine (manufactured by Matsuo Sangyo Co., Ltd., product name "K Printing Proofer") equipped with a gravure engraving plate with a mesh of 175 lines / inch (33 μm), and the resulting product was dried with hot air at 80°C for 10 seconds to form a printed layer (thickness: 2 to 8 μm), thereby obtaining a printed matter (laminate). The product was then aged at 40°C for 48 hours.

[0085] <Evaluation of friction coefficient> The printed surfaces of the aged prints were placed together, and the prints were slid against each other under conditions of a load of 200 g and a speed of 100 mm / min in accordance with JIS K 7125 to measure the static and dynamic friction coefficients. The preferred value of the static friction coefficient is as described above. The dynamic friction coefficient is preferably 0.5 or more, and more preferably 0.6 or more.

[0086] <Evaluation of slip angle> The printed surfaces of the aged prints were placed together, and the sliding angle was measured using a friction measuring instrument (manufactured by Toyo Seiki Co., Ltd., product name "Friction Measuring Instrument AN") in accordance with JIS P 8147:2010 "8 Inclination Method." The sliding angle is preferably equal to or greater than 30°, and more preferably equal to or greater than 35°.

[0087] <Evaluation of adhesion to substrate> After aging, cellophane tape (manufactured by Nichiban Co., Ltd.) was applied to the printed surface of the printed material, and the cellophane tape was quickly peeled off. The condition of the printed layer remaining on the substrate was visually inspected, and the adhesion to the substrate was evaluated according to the evaluation criteria shown below. 5: The ratio of the area of ​​the peeled off printing layer to the total area of ​​the printing layer is 0% or more and less than 5%. 4: The ratio of the area of ​​the peeled off printing layer to the total area of ​​the printing layer is 5% or more and less than 20%. 3: The ratio of the area of ​​the peeled off printing layer to the total area of ​​the printing layer is 20% or more and less than 50%. 2: The ratio of the area of ​​the peeled off printing layer to the total area of ​​the printing layer is 50% or more and less than 80%. 1: The ratio of the area of ​​the peeled off printing layer to the total area of ​​the printing layer is 80% or more and 100% or less.

[0088] <Evaluation of blocking resistance> The printed surface of a printed item immediately after production (before aging) was placed on the non-printed surface of the same printed item and subjected to a pressure of 4 kg / cm 2 A load of 1000 kg was applied and the sample was stored in a thermostatic chamber at 40° C. for 24 hours. The printed and non-printed surfaces were then peeled away, and the state of adhesion of the printed layer to the non-printed surface (ink removal) was visually confirmed, and the blocking resistance was evaluated according to the following evaluation criteria. 5: Ink absorption onto non-printed surfaces is greater than 0% and less than 10% of the total area of ​​the printed layer. 4: Ink absorption onto non-printed surfaces is greater than 10% and less than 20% of the total area of ​​the printed layer. 3: Ink absorption onto the non-printed surface is greater than 20% and less than 50% of the total area of ​​the printed layer. 2: Ink absorption onto the non-printed surface is greater than 50% and less than 80% of the total area of ​​the printed layer. 1: Ink absorption onto the non-printed surface is 80% or more and 100% or less of the total area of ​​the printed layer.

[0089] <Evaluation of heat resistance> The printed surface of the aged print was placed on soft aluminum foil, and a heat seal tester (manufactured by Tester Sangyo Co., Ltd., product name "TP-701-C Heat Seal Tester") was used to test the print at 140 to 180°C and 2 kg / cm from the aluminum foil. 2 After that, the printed surface was peeled off from the aluminum foil, and the state of ink transfer onto the aluminum foil was visually confirmed, and the heat resistance was evaluated according to the following evaluation criteria. 5: The ink did not come off even when heated to 180℃. 4: When heated to 170°C, the ink did not come off, but when heated to 180°C, the ink did come off. 3: When heated to 160°C, the ink did not come off, but when heated to 170°C, the ink did come off. 2: When heated to 150℃, the ink did not come off, but when heated to 160℃, the ink did come off. 1: Ink removal occurred when heated below 150℃.

[0090] <Evaluation of abrasion resistance> A friction test was performed on the printed surface of the aged print using a Gakushin-type friction fastness tester (manufactured by Tester Sangyo Co., Ltd., product name "AB-301"), in which the surface was rubbed back and forth 100 times with a black cloth (cotton No. 3-1: gold cloth No. 3) under a load of 200 gf. The appearance of the printed layer was then visually confirmed, and the friction resistance was evaluated according to the following evaluation criteria. 5: The percentage of the area of ​​the printed layer that has transferred to the black cloth (gold cloth No. 3) is greater than 0% and less than 10%. 4: The percentage of the area of ​​the printed layer that has transferred to the black cloth (gold cloth No. 3) is greater than 10% and less than 20%. 3: The percentage of the area of ​​the printed layer that has transferred to the black cloth (gold cloth No. 3) is greater than 20% and less than 50%. 2: The area of ​​the printed layer that has transferred to the black cloth (gold cloth No. 3) is 50% or more and less than 80%. 1: The percentage of the area of ​​the printed layer that has transferred to the black cloth (gold cloth No. 3) is 80% or more and 100% or less.

[0091] <Evaluation of printability> The prepared ink composition was diluted with the same organic solvent (C) as that blended in the ink composition so that the viscosity at 25°C measured using Zahn cup #3 was 17 seconds. The diluted ink composition was fed into the ink pan of a five-color gravure printing machine (manufactured by Fuji Machine Industry Co., Ltd.) equipped with a commercially available steel doctor blade and a plate with only non-printing areas, and the plate was run idle at 150 m / min for 30 minutes. Thereafter, the occurrence of streaky stains (doctor streaks) on the plate surface was visually confirmed, and the printability was evaluated according to the following evaluation criteria. 5: No doctor streaks or 1-2 faint doctor streaks were observed. 4: Three to five thin doctor lines were observed. 3: Six or more faint doctor streaks or one or two dark doctor streaks were observed. 2: Three to five thick doctor streaks were identified. 1: Six or more thick doctor lines were identified.

[0092] The evaluation results are shown in Tables 1 to 5.

[0093] [Table 1]

[0094] [Table 2]

[0095] [Table 3]

[0096] [Table 4]

[0097] [Table 5]

[0098] As shown in the above results, the printed layers formed from the ink compositions of Examples 1 to 16 were excellent in non-slip properties (static friction coefficient, dynamic friction coefficient, sliding angle), adhesion to the substrate, blocking resistance, heat resistance, and abrasion resistance. In addition, these ink compositions were also excellent in printability. On the other hand, Comparative Example 1, in which the average particle size of the urethane resin beads (B) was less than 1.5 μm, was inferior in non-slip properties. Comparative Example 2, in which the average particle size of the urethane resin beads (B) exceeded 16 μm, was inferior in adhesion to the substrate, blocking resistance, heat resistance, abrasion resistance, and printability. Comparative Example 3, in which the urethane resin beads (B) had a glass transition temperature of less than -20°C, was poor in blocking resistance and heat resistance. Comparative Example 4, in which the urethane resin beads (B) had a glass transition temperature of more than 25° C., was inferior in non-slip properties. Comparative Examples 5 and 6, which used resin beads other than urethane resin beads, were inferior in non-slip properties. Comparative Example 7, which did not contain the urethane resin beads (B), was inferior in non-slip properties. Comparative Examples 8 and 10, in which (B) / (A) was less than 0.1, were inferior in non-slip properties. Comparative Examples 9 and 11, in which (B) / (A) was more than 1.5, were inferior in adhesion to the substrate, blocking resistance, heat resistance, abrasion resistance, and printability. [Industrial Applicability]

[0099] The printing ink composition of the present invention can form a printed layer that is excellent in non-slip properties, adhesion to a substrate, blocking resistance, heat resistance, and abrasion resistance. The printing ink composition of the present invention also has excellent printability. The printing ink composition of the present invention is particularly useful for gravure printing.

Claims

1. A printing ink composition (excluding aqueous ink compositions) containing a binder resin (A), urethane resin beads (B), and an organic solvent (C), the binder resin (A) contains at least two resins selected from the group consisting of polyurethane resins, vinyl chloride-vinyl acetate copolymers, and (meth)acrylic resins; The urethane resin beads (B) have an average particle size of 1.5 to 16 μm and a glass transition temperature of −20 to 25° C., a ratio of the mass of the urethane resin beads (B) to the mass of the binder resin (A) calculated as a solid content is 0.1 to 1.5; A printing ink composition, wherein the content of the binder resin (A) in terms of solid content is 20 to 58 mass % based on the solid content of the printing ink composition.

2. 2. The printing ink composition according to claim 1, wherein the content of the binder resin (A) in terms of solid content is 5 to 30 mass % based on the total mass of the printing ink composition.

3. 2. The printing ink composition according to claim 1, wherein the static friction coefficient between printed surfaces of a printed matter obtained by forming a printed layer on a plastic film using the printing ink composition is 1.0 or more.

4. 2. The printing ink composition according to claim 1, further comprising a hydrocarbon wax.

5. 2. The printing ink composition according to claim 1, further comprising silica, the content of said silica being 1 to 10 mass % based on the solid content of said printing ink composition.

6. 2. The printing ink composition according to claim 1, further comprising a fatty acid amide, the fatty acid amide content being 0.5 to 5 mass % based on the solid content of the printing ink composition.

7. 2. The printing ink composition according to claim 1, further comprising a terpene resin, the content of the terpene resin being 0.5 to 10 mass % based on the solid content of the printing ink composition.

8. The printing ink composition according to claim 1, further comprising a curing agent.

9. 2. The printing ink composition according to claim 1, wherein the organic solvent (C) contains at least two solvents selected from the group consisting of ester-based solvents, ketone-based solvents and alcohol-based solvents.

10. 2. The printing ink composition according to claim 1, which is for gravure printing.

11. A plastic film; A printing layer formed from the printing ink composition according to any one of claims 1 to 10 on the plastic film; A laminate comprising:

12. A packaging material comprising the laminate according to claim 11.

Citation Information

Patent Citations

  • Coating agent composition for printing and printed matter

    JP2017171910A

  • Film having scratch resistance and surface coating composition

    JP2019123782A

  • film

    JP2020175539A

  • Ink composition, laminate, and food packaging material

    JP2022166508A

  • Water-based ink compositions for surface printing and articles with printing layer

    JP2023087437A

Cited By

  • Non-slip coating varnish composition and coated product

    JP2026156535A

  • Non-slip coating varnish composition and coated product

    JP2026156546A